The knowledge and opinions of health professionals working in the first level health care instutions about the program of fluor tablet usage to improve mouth and teeth health - GENC, Metin; PEHLIVAN, Erkan; GUNES, Gulsen; EGRI, Mucahit; KURCER, M.Ali (Annals of Medical Research, 2021)
None
Keywords: s : Fluor, children.